SEPTICEMIC CUTANEOUS ULCERATIVE DISEASE IN A MULTI-SPECIES COLLECTION OF SEMI-AQUATIC TURTLES - Lescano G., Jesús (2013)
Septicemic cutaneous ulcerative disease (SCUD) is a common problem in immunocompromised chelonians, which is usually associated to poor environmental quality and skin lesions. It is reported the case of a mixed group of semi-aquatic turtles conformed by two yellow-spotted river turtle (Podocnemis unifilis) and five red-eared slider turtles (Trachemys scripta) reared in a poor quality enclosure. The two P. unifilis showed severe clinical signs compatible with SCUD (erythema, skin erosions, lethargy and anorexia) whereas only two T. scripta showed mild signs of disease (erythema). The two P. unifilis were treated with enrofloxacin (10 mg/kg, subcutaneous, every 24 h) and the enclosure for the other animals was improved. One P. unifilis died at the second day of the treatment but the second turtle fully recovered in 14 days.